2016
DOI: 10.1038/nature17196
|View full text |Cite
|
Sign up to set email alerts
|

Recent near-Earth supernovae probed by global deposition of interstellar radioactive 60Fe

Abstract: The rate of supernovae (SNe) in our local galactic neighborhood within a distance of ~100 parsec from Earth (1 parsec (pc)=3.26 light years) is estimated at 1 SN every 2-4 million years (Myr), based on the total SN-rate in the Milky Way (2.0±0.7 per century1,2). Recent massive-star and SN activity in Earth’s vicinity may be evidenced by traces of radionuclides with half-lives t1/2 ≤100 Myr3-6, if trapped in interstellar dust grains that penetrate the Solar System (SS). One such radionuclide is 60Fe (t1/2=2.6 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
607
5
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(654 citation statements)
references
References 29 publications
32
607
5
2
Order By: Relevance
“…Feige (2014) found the signal to extend in time beyond the Knie et al (2004) time interval with a total time-integrated fluence of ( )  = ´-2.32 0.60 10 atoms cm Feige 7 2 . In addition, Wallner et al (2016) found a larger total time-integrated value of  = Wallner ( ) ´-3.5 0.2 10 atoms cm 7 2 . For the purposes of this paper we will focus solely on the fluences that overlap with the Knie et al fluence.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Feige (2014) found the signal to extend in time beyond the Knie et al (2004) time interval with a total time-integrated fluence of ( )  = ´-2.32 0.60 10 atoms cm Feige 7 2 . In addition, Wallner et al (2016) found a larger total time-integrated value of  = Wallner ( ) ´-3.5 0.2 10 atoms cm 7 2 . For the purposes of this paper we will focus solely on the fluences that overlap with the Knie et al fluence.…”
Section: Introductionmentioning
confidence: 96%
“…These studies have considerable overlap in their time periods and greatly varying locations onEarth. We do not examine the Wallner et al (2016) measurements in detail, first, because the bulk of the analysis for this paper was completed and submitted for review prior to the publication of Wallner et al (2016), and second, because many of the samples included in Wallner et al (2016) arealready included in the other studies, do not cover the period around the 2.2 Myr signal, or were drawn from similar latitudes tothe other samples.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports provide evidence of a 2.2 Myr old supernova at a distance between 60-130 pc based on measurements of 60 Fe deposition on the ocean floor (Binns et al 2016;Breitschwerdt et al 2016;Wallner et al 2016) and on the Moon (Fimiani et al 2016). They also report the possibility of 16 events in the past 13 My within 100 pc in the Local Bubble.…”
Section: Nearby Supernovaementioning
confidence: 99%
“…They also report the possibility of 16 events in the past 13 My within 100 pc in the Local Bubble. They estimate the frequency of such nearby explosions, with at least one event occurring every 2-4 My based on SN rate of ∼ 2 events/century (Wallner et al 2016). On longer timescales of ∼ Gyr, one can assume that a large number of such events would have deposited energy in the Martian atmosphere.…”
Section: Nearby Supernovaementioning
confidence: 99%